(untitled) (Studia austriaca, 2021)
The following article reconstructs the almost 25-year-long relationship between the two fin de siècle poets Arthur Schnitzler and Richard Dehmel. The analysis is based on the assumption that the rival “artist friendship” is determined by a constitutive generic competition. Schnitzler admired Dehmel’s genius in forms of poetry that he himself had not mastered, first and foremost lyric poetry, but otherwise regarded him critically where he himself had succeeded, namely in the genre of drama. This early resentment forms a lifelong paradigm of Schnitzler’s perception of Dehmel and prevented a sincere appreciation of Dehmel as an artistic equal.